Water hyacinth conversion to biochar for soil nutrient enhancement in improving agricultural product - Yezbie Kassa; Agmas Amare; Tayachew Nega; Teferi Alem; Mohammed Gedefaw; Bilhate Chala; Bernhard Freyer; Beatriz Waldmann; Tarekegn Fentie; Tewodros Mulu; Taddesse Adgo; Gizachew Ayalew; et al. (Scientific Reports)
Abstract The conversion of water hyacinth into biochar offers a sustainable solution to mitigate its proliferation and enhances its potential as a soil amendment for agriculture. This study examined the physicochemical properties of water hyacinth biochar (WHBC) and its impact on soil fertility. Water hyacinth (Eichhornia crassipes) was pyrolyzed at 300 °C for 40 minute with restricted airflow (2–3 m/s), producing biochar with desirable properties and a yield of 44.6%. WHBC exhibited a pH of 8.11 ± 0.91, electrical conductivity of 18.70 ± 1.15 mS/cm, and nutrient contents including TN (0.69 ± 0.10%), TP (8.80 ± 0.01%), OC (13.95 ± 0.65%), C/N ratio (20.22 ± 0.95), S (0.34 ± 0.03%), and metallic nutrients (Ca, Mg, K). Heavy metals (Fe, Mn, Cu, Ni, Cd, Pb, Cr, Zn) were within permissible limits for biochar. Soil amended with 2500 kg/ha WHBC (BC2) produced comparable Teff crop yields (fresh mass: 1191.67 ± 428.44 g, dry mass: 700.00 ± 248.34 g, grain yield: 95.00 ± 39.69 g) to those with mineral fertilizers and mixed amendments. Fourier Transform Infrared (FTIR) and Scanning Electron Microscopy (SEM) revealed significant structural changes in WHBC, enhancing its pore structure and surface morphology. These results demonstrate the potential of WHBC as an effective soil amendment to improve agricultural sustainability and soil fertility.